Analysis of Fishermen’s Participation in the Revitalization of the Capture Fisheries Sector Through a Community Agribusiness Model in Tanjung Bulan Village, Tanjung Kemuning Subdistrict, Kaur Regency - Elham Cahyadi (Journal of Multidisciplinary Research, 2026)
An Analysis of Fishermen's Participation in the Revitalization of Capture Fisheries Businesses Through a Community Agribusiness Model in Tanjung Bulan Village, Tanjung Bulan Sub-District, Kaur Regency. Tanjung Bulan Village, Tanjung Kemuning Sub-District, Kaur Regency is one of the coastal areas that has fishermen's businesses in the management of fishery resources and the revitalization of capture fisheries businesses through an agribusiness model. The research method used a descriptive method with a mixed approach (qualitative and quantitative). Data collection was carried out through direct observation, interviews, and questionnaires with a Likert scale, and supported by secondary data from journals and other references. The results show: (1) The level of fishermen's participation is in the high category (index 71.5); (2) The level of business revitalization is in the very high category (index 85.17) with significant improvements in the dimensions of production, marketing, financial management, and supporting facilities.